Acutolysin C, a weak hemorrhagic toxin from the venom of Agkistrodon acutus with leucoagglutination activity - Wei,CB (2011)
The properties and agglutination activity of acutolysin C, a hemorrhagic metalloproteinase obtained from Agkistrodon acutus venom, were studied herein. Acutolysin C is a basic glycoprotein consisting of a single polypeptide chain with a molecular weight of 23.1 kDa and pI 8.7, containing one Zn2+ and one Ca²+ per molecule. It possesses caseinolytic, weak lethal (LD50 = 7.6 mg/kg) and weak hemorrhagic (MHD = 12.0 μg) activities, but does not present fibrinolytic, fibrinogenolytic, arginine esterase and phospholipase A2 actions. In addition, it revealed agglutination activity on some animal lymphocytes, including five species of mammals, six of birds, three of reptiles and one of amphibians, but had no effect on lymphocytes from two species of reptiles, one amphibian and nine species of fish. It had no effects on the erythrocytes and platelets of all 26 animal species tested. Both leucoagglutination and caseinolytic activities were inhibited by EDTA; while cysteine, 2-mercaptoethanol, 1,4-dithiothreitol, glutathione, serum against acutolysin C and serum against homologous snake venom as well as glucose, sucrose, mannose, lactose and galactose had no effects on inhibition. The lowest concentration of acutolysin C that induced mouse lymphocyte agglutination was 2.5 μg/mL. Acutolysin C is an interesting substance since it is the first member of the hemorrhagin family to be shown to have leucoagglutination activity.